A Comparative Study of English Language Teachers’ Motivational Strategies in State and Private Primary Schools - Iyehezkiel (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2025)
This study investigates the differences in motivational strategies employed by English language teachers in state and private primary schools in Indonesia. Grounded in Dörnyei’s L2 Motivational Self System and Henry’s three-level model of language learning motivation, the research aims to examine both the perceived importance and frequency of use of specific motivational strategies in classroom settings. Using a survey-based quantitative method, data were collected from 200 English teachers across 32 primary schools in Tangerang Selatan during the 2024–2025 academic year. Two questionnaires, adapted from Dörnyei and Csizér’s (1998) framework, assessed teachers’ beliefs and practices regarding 30 motivational strategies. Results from independent samples t-tests indicate no significant difference between the two groups in terms of the importance attributed to motivational strategies. However, private school teachers reported significantly more frequent use of diverse, student-centered strategies, particularly those involving authentic materials, group work, and cultural content. The findings highlight the impact of institutional resources, class size, and teacher autonomy on motivation practices. Implications suggest the need for increased support for state school teachers through resource provision and professional development focused on motivational pedagogy.